A case of successful treatment of tracheoesophageal fistula using laser exposure - E. N. Novozhilova; V. I. Popadyuk; S. A. Sokolov; I. F. Chumakov; A. I. Chernolev (Опухоли головы и шеи)
The study objective – to present a unique clinical observation of the successful treatment of tracheoesophageal fistula using laser exposure.Case report. Patient H., 51 years old, applied to the Moscow City Oncology Hospital No 62, Moscow Healthсare Department on January 22, 2018, with a diagnosis of thyroid cancer (multicentric growth), T3N0M0 (hospital No. 1974 / 43). Thyroidectomy was performed on 03.08.2009, removal of a recurrent tumor with resection of the esophageal wall and trachea – 03.02.2021. Histological examination No. 5589 / 56662–56668 dated 09.02.2021: papillary cancer with invasion of the wall of the esophagus and trachea. Resection within unaltered tissues. A mobilized sternocleidomastoid muscle was used to separate the esophagus and trachea. A nasogastric tube was used for 14 days. The wound on the neck healed by primary intention. The patient began to eat through the mouth. A day after the removal of the probe, facial emphysema began to grow intensively, which was accompanied by a cough. The nasogastric tube is reinserted. With fluoroscopy of the esophagus and with pharyngogastroduodenoscopy, a tracheoesophageal fistula was revealed along the right lateral wall of the trachea, about 0.5 cm in size, 1.5–2 cm below the level of the vocal folds. On endoscopic examination a week later, the fistula was already 1.0 cm in size. Conservative therapy and surgical treatment were carried out. Due to the flexible laser fiber, a phased effect on the fistula wall was carried out, both from the esophagus and from the trachea. Within a week after the first session, the fistulous opening decreased by 2 times. Then 2 more sessions were carried out with an interval of 10 days. During endoscopic examination from 05.05.2021 the fistula between the trachea and the esophagus is not defined. The mucous membrane is epithelized, smooth. Swallowing is free.Conclusion. Thus, the problem of treating patients with tracheoesophageal fistulas is extremely complex and versatile. The localization of the fistula, its size, and the clinic’s capabilities for treating a patient are of great importance.